Children’s perspectives in times of COVID-19 towards the impact on their participation in preschool - Ólafsdóttir, Sara M.; Karlsdóttir, Kristín; Sigurjónsdóttir, Díana Lind (Menntavísindasvið Háskóla Íslands, 2021)
We are living in an unparalleled time of a pandemic that has affected communities all over the world, and the school system has not been spared. Different measures have been implemented, and in some countries, preschools and primary schools were closed to reduce the spread of the disease and protect the health care system. The closing of schools has affected the education of 80% of children in the world. In Iceland, the Ministry of Health decided not to close the schools. Instead, restrictions on their operations were imposed. This decision was made because children seemed to be less affected by the virus than did adults. It was considered important to keep the schools open so that children could have access to education and care and maintain their daily routines. The restrictions recommended were for schools to reduce the number of children in groups and to separate groups over a period to lower the risk of infection. In preschools, the groups were separated by allocating days for each group to come to the preschool. Consequently, children were not able to attend the preschool every day. However, exceptions were made for children in vulnerable groups and those whose parents were front-line workers.The aim of this study is to explore how the children experienced changes made in the preschool during the first wave of the pandemic. The purpose is to learn from the children and use the knowledge created to support children and the planning of the preschool environment in unprecedented times. The research builds on the idea that children are competent persons who construct their knowledge in collaboration with other children and adults. They have the right to be active participants in society and influence their daily lives.The research was conducted in one preschool in Iceland. Daily, 120 children attend the preschool in six classes. During the restrictions, only half of the children could attend the school. Twenty-three children, aged three to six years, participated in the study. The children took part in group ...